Synthesis of Novel Tetraazamacrocyclic Bisquinoline Derivatives as Potential Antimalarial Agents - N.-A. Amoyaw, Prince; Pham, Ken; N. Cain, Amy; M. McClain, James; J. Hubin, Timothy; Faruk Khan, M.O. (Current Organic Synthesis, 2014)
Novel bisquinoline derivatives of tetraazamacrocyclic compounds, namely 4,10-bis(7-chloroquinoline)-1,4,7,10-tetraazacyclododecane (1, Scheme 1); 4,10-bis(7-chloroquinoline)-1,7-dimethyl-1,4,7,10-tetraazacyclododecane (6, Scheme 2); 4,11-bis(7-chloroquinoline)- 1,4,8,11-tetraazabicyclo[6.6.2]hexadecane (6a, Scheme 3) and 4,10-bis(7-chloroquinoline)-1,4,7,10-tetraazabicyclo[5.5.2] tetradecane (6b, Scheme 3) which are potential antimalarial drugs have been synthesized. The macrocycle framework had to be modified to allow attachment of the substituent (4,7-dichloroquinoline) at the nitrogen atom. The initial synthesis of (1) by direct derivatization was inefficient for selective functionalization and consequently the desired product was isolated in low yield. We have found that by choosing N-methylpyrrolidinone as the reaction solvent, with triethylamine as base, and elevating the reaction temperature, product (1) was accessed with yields of up to 45%. Compounds 6, 6a and 6b were synthesized via regioselective modification of the macrocyclic framework before the attachment of the 4,7-dichloroquinoline substituent.
Keywords: Bisquinoline